Pelatihan Membaca Bagi Peserta Didik SD Kristen Petra Alak Dalam Program Kampus Mengajar Angkatan 3 - Nelssy Salut, Karolina; Dizyah Apriyati Here, Ananda; Kristiana Hina, Yane; Isantri Neolaka, Ofilda; Fandira Atonis, Marni; Dewa, Egidius (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This paper focuses on the reading training program for students of SD Kristen Petra Alak conducted by participants of the Kampus Mengajar Angkatan 3. The purpose of this training is to improve students' reading skills through reading. This training is expected to provide positive benefits for students in developing their reading skills. The method used in this reading training is to use creative and interactive methods such as storytelling, singing, and role-playing. Learners are also given reading materials that are suitable for their grade level, namely, grade 2 to grade 4. Of the 25 learners who participated in the reading training program, the average reading ability was 57% with a sufficient category. The teacher's response to the implementation of the reading training program was 83% with the Satisfied category while the response of Petra Alak Christian Elementary School students to the implementation of the reading training program was 82% with the Satisfied category. The results of this activity show that effective reading training strategies can help learners improve their reading skills this can be seen from the good responses given.